Art sleeves : album covers by artists - Burkeman, DB (Rizzoli International Publications, Inc., 2021)
"Art Sleeves is a time capsule of visual art and music culture as shown through the most important record covers designed by visual artists and graphic designers in the past forty years. This tightly curated collection of covers chosen includes works with significant cultural impact as well as collaborations that themselves created cultural fascination. The eclectic roster of visual artist-musician collaborations presented spans art and musical genres as well as generations, including Ryan McGinley for Sigur Rós, Kara Walker for Arto Lindsay, Peter Saville for Joy Division, Barbara Kruger for Growing Up Skipper, Jeff Koons for Lady Gaga, Tauba Auerbach for Glasser, and Stanley Donwood for Radiohead, to name a few. From postmodernist paintings and minimalism to collage and photography, as well as New Wave, emo, pop, and punk, the albums chosen present a bright and rich visual and cultural history. This inspiring volume celebrates this long creative tradition of visual artist-musician collaborations and, just like a perfect album, it will be treasured by art, music, and record lovers alike." --Amazon.com.